A Bowen ratio-informed method for coordinating the estimates of air–sea turbulent heat fluxes - Yizhe Wang; Ronglin Tang; Lingxiao Huang; Meng Liu; Yazhen Jiang; Zhao-Liang Li (Environmental Research Letters, 2024)
Accurate quantification of turbulent heat fluxes [THF, comprising sensible heat flux (SHF) and latent heat flux (LHF)] and Bowen ratio ( β , ratio of SHF and LHF) is essential for understanding the air–sea interaction. However, the biased estimates of SHF and LHF by widely applied bulk aerodynamic models, and the separate estimates of SHF and LHF by data-driven models, both may result in unrealistic β estimates. This study for the first time innovatively proposes a Bowen ratio-informed data-driven model (BrTHF) for coordinating the estimations of THF and β using the multivariate random forest (RF) technique and a combination of eddy covariance flux observations and meteorological and oceanic observations collected from 53 historical cruises. The result shows that the BrTHF model could not only achieve high-accuracy SHF and LHF estimates, but also avoid the outliers of β estimates that were commonly found in un-synergistic RF and well-known Coupled Ocean Atmosphere Response Experiment 3.5 models.